Case Report: Severe gastric atrophy associated with a novel homozygous variant in LRBA - Yuan, Shilin; Li, Ting; Tong, Yu; Wang, Zhiling (Frontiers in Pediatrics, 2025)
BackgroundThe prevalence of atrophic gastritis is challenging to determine, considering that it is typically asymptomatic and that its definition and diagnosis vary among studies. Furthermore, gastric atrophy is underreported and is often considered an underdiagnosed condition in pediatrics.Case summaryThis report describes the case of a 13-year-old girl who initially presented with autoimmune hemolytic anemia, followed by extensive severe gastric mucosal atrophy and erosions with severe growth retardation inconsistent with autoimmune gastritis (AIG). To our knowledge, this represents the first documented case of such an extensive and severe atrophic gastritis identified in Sichuan Province, China. Genetic analysis revealed that the patient exhibited a homozygous mutation in c.229_230del; p.Gln77Valfs*2:NM_001364905.1 in the gene encoding the lipopolysaccharide-responsive beige-like anchor protein (LRBA). This mutation led to the loss of normal protein function via nonsense-mediated decay of mRNA or premature termination of the encoded amino acid sequence. This case elucidates a distinct and severe phenotype form of atrophic gastritis caused by the c.229_230del; p.Gln77Valfs*2 homozygous mutation in LRBA, expanding the clinical spectrum of LRBA deficiency.ConclusionOur findings may provide insight into the study of the mechanism of atrophic gastritis and the diagnosis and treatment of severe forms of this condition in pediatric patients.